Step by step illustrative video of laparoscopic artificial urinary sphincter implantation in a woman with recurrent stress urinary incontinence - Cordeiro, Agostinho (2019)
[Excerpt] Stress urinary incontinence (SUI) is the most common subtype of incontinence and is defined as the perception of urine loss with effort. In most cases, it is due to insufficient support of the bladder neck, urethral hypermobility, and in a minority of cases, intrinsic sphincter deficiency (ISD). Sometimes both pathophysiological mechanisms occur simultaneously.[...]